2018
DOI: 10.1128/aem.01401-17
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of Primary Metabolism and Xenobiotic Mitigation Characterizes the Proteome of Bjerkandera adusta during Wood Decomposition

Abstract: The aim of the current work was to identify key features of the fungal proteome involved in the active decay of beechwood blocks by the white rot fungus Bjerkandera adusta at 20°C and 24°C. A combination of protein and domain analyses ensured a high level of annotation, which revealed that while the variation in the proteins identified was high between replicates, there was a considerable degree of functional conservation between the two temperatures. Further analysis revealed differences in the pathways and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Bjerkandera adusta, was a white rotting fungi growing on branch and fallen wood. Recent studies have focused on its enzymatic properties and application, such as laccase synthesis [21], lignocellulose decomposition [17], biodegradation of synthetic dyes [16,22] and the wastewater treatment [23]. In contrast, few reports have been done if B. adusta could control the fusarium wilt disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bjerkandera adusta, was a white rotting fungi growing on branch and fallen wood. Recent studies have focused on its enzymatic properties and application, such as laccase synthesis [21], lignocellulose decomposition [17], biodegradation of synthetic dyes [16,22] and the wastewater treatment [23]. In contrast, few reports have been done if B. adusta could control the fusarium wilt disease.…”
Section: Discussionmentioning
confidence: 99%
“…Bjerkandera adusta, a white rot fungus belonging to the family Polyporaceae, generally parasitizes on plant branch, fallen or dead trees [16,17]. At present, studies on Bjerkandera adusta primarily focus on the production of laccase, lignocellulose decomposition [18], and degradation of organic pollutants such as daunomycin and humic acids [19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a large scale analysis comparing 62 fungal genomes, revealed that 409 gene families appear to be evolutionarily correlated with white rot, including families related to both decay and detoxification processes (Nagy et al ., ). Accordingly, transcriptomic and proteomic approaches validated this co‐induction of decaying and detoxification genes and proteins at the functional level during the lignolytic process (Korripally et al ., ; Kameshwar and Qin, ; Miyauchi et al ., ; Moody et al ., ). To better understand the toxic effect of wood extractives, we have previously analysed global gene expression of Phanerochaete chrysosporium in presence of oak extractives for 24 h (Thuillier et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Once lignin polyphenolic structure presents similarities with many aromatic pollutants, microbial ligninolytic systems have been extensively studied in the last years, searching for potential tools for bioremediation of contaminated sites and for a better understanding of the environmental fate of toxic compounds [5,6]. Recent proteomic approaches concluded that wood decay, itself, is a source of toxic phenolic derivatives and reactive oxygen species; thus, ligninolytic and stress response enzymes are expressed simultaneously [7]. White-rot fungi are the main producers of non-speci c oxidases that can act upon a wide range of substrates.…”
Section: Introductionmentioning
confidence: 99%